Effectiveness of Cyriax massage on rom increase in adult patients with tenosinovitis of quervain (Revista Chilena de Rehabilitación y Actividad Física, 2022)
Cyriax is a therapeutic massage that produces in areas proximal to the tendon insertions a controlled inflammation that restores the properties of the injured connective tissue, there is scientific evidence of its positive effects in patients with tendinopathies that cause pain and limitation of movement. Quervain tenosynovitis is a common tendinopathy that causes stenosis of the tendons of the abductor pollicis longus and extensor pollicis brevis, causing the set of symptoms described above. Objective: To collect updated information on the efficacy of Cyriax massage in increasing range of motion (IRM) in patients with Quervain Tenosynovitis. Materials and methods: A bibliographic review of the scientific literature published between 2009 and 2021 is carried out in various databases: Medline, PubMed, Scielo, The Cochrane Library, Elsevier, Embase. Results: 15 articles were selected that compare the Cyriax Massage with other techniques to demonstrate its effectiveness in the management of IRM, the results are positive for the increase in IRM and decrease in pain. Conclusion: Cyriax massage is efficient in reducing pain and increasing IRM. However, the heterogeneity of the studies, measurement instruments, and / or design do not allow definitive conclusions to be drawn about the technique as the only treatment route.
Keywords: Quervain tenosynovitis; deep transverse massage; tendinitis; manual therapies; Cyriax massage